The Economic Impact of Parasitism from Nematodes, Trematodes and Ticks on Beef Cattle Production - Tom Strydom; Robert P. Lavan; Siddhartha Torres; Kathleen Heaney (Animals, 2023)
Global human population growth requires the consumption of more meat such as beef to meet human needs for protein intake. Cattle parasites are a constant and serious threat to the development of the beef cattle industry. Studies have shown that parasites not only reduce the performance of beef cattle, but also negatively affect the profitability of beef agriculture and have many other impacts, including contributing to the production of greenhouse gases. In addition, some zoonotic parasitic diseases may also threaten human health. Therefore, ongoing cattle parasite research is crucial for continual parasite control and the development of the beef cattle industry. Parasitism challenges profitable beef production by reducing feed efficiency, immune function, reproductive efficiency, liveweight, milk yield, calf yield and carcass weight, and leads to liver condemnations and disease transmission. Globally, beef cattle producers incur billions (US$) in losses due to parasitism annually, with gastrointestinal nematodes (GIN) and cattle ticks causing the greatest economic impact. The enormity of losses justifies parasitic control measures to protect profits and improve animal welfare. Geographical differences in production environment, management practices, climate, cattle age and genotype, parasite epidemiology and susceptibility to chemotherapies necessitate control methods customized for each farm. Appropriate use of anthelmintics, endectocides and acaricides have widely been shown to result in net positive return on investment. Implementing strategic parasite control measures, with thorough knowledge of parasite risk, prevalence, parasiticide resistance profiles and prices can result in positive economic returns for beef cattle farmers in all sectors.